2021
DOI: 10.3390/met11030442
|View full text |Cite
|
Sign up to set email alerts
|

Residual Flexural Capacity of Corroded Prestressed Reinforced Concrete Beams

Abstract: Infrastructures and industrial buildings are commonly exposed to aggressive environments and damaged by corrosion. In prestressed reinforced concrete structures, the potential risks of corrosion could be severe since reinforcements are already subjected to high amounts of stress and, consequently, their load-bearing capacity could abruptly decrease. In recent years, some experimental studies have been conducted to explore the flexural behavior of corroded pretensioned reinforced concrete (PRC) beams, investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 50 publications
(141 reference statements)
0
17
0
Order By: Relevance
“…Post-1980 scientific reports and technical documents [26][27][28] give a great emphasis to the reduced service life of RC structures in relation to bar corrosion and carbonation. In several papers, carbonation is regarded among the primary detrimental factors responsible for the corrosion of bars and the reduction of the service life of concrete structures [29][30][31][32], while many others investigated the reduction of the strength capacity of RC structures due to corrosion (see, e.g., [33][34][35][36]).…”
Section: Some Divergencies Between Past and Present On Rc Durabilitymentioning
confidence: 99%
“…Post-1980 scientific reports and technical documents [26][27][28] give a great emphasis to the reduced service life of RC structures in relation to bar corrosion and carbonation. In several papers, carbonation is regarded among the primary detrimental factors responsible for the corrosion of bars and the reduction of the service life of concrete structures [29][30][31][32], while many others investigated the reduction of the strength capacity of RC structures due to corrosion (see, e.g., [33][34][35][36]).…”
Section: Some Divergencies Between Past and Present On Rc Durabilitymentioning
confidence: 99%
“…Five research papers have been published in Special Issue of Metals titled Corrosion Effects on the Durability of RC Structures. The collected articles deal with several aspects of the corrosion phenomenon in reinforced concrete, including the copper corrosion behavior in simulated concrete-pore solutions [1], the influence of microstructure on the corrosion resistance of steel bars and their fatigue behavior [2], the degradation of bond mechanism between steel and concrete [3,4], and the flexural capacity of corroded Prestressed Reinforced Concrete (PRC) beams [5].…”
Section: Contributionsmentioning
confidence: 99%
“…Especially in the case of prestressed reinforced concrete (PRC) structures, the potential corrosion risks could be severe since steel reinforcements are already subjected to high amounts of stress and, consequently, their load-bearing capacity could abruptly decrease. M. Kioumarsi et al [5] presented an extensive review of the available experimental research on the load-bearing capacity of corroded PRC beams. The outcomes demonstrate that corrosion in PRC beams results in pitting corrosion in the strands, developing stress concentration around the pits, which induces the premature failure of prestressing wires.…”
Section: Contributionsmentioning
confidence: 99%
“…Additionally, such parameters as the concrete type, the effect of aging and their impact on the diffusion coefficient are analyzed. Interesting is the work [ 9 ], where on the basis of the profound theoretical research degradation, the law for the flexural strength of corroded PRC beams is suggested.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%